LANGUAGE TRAVEL SUPPLY: LANGUAGE TOURISM PRODUCT COMPOSITION - Montserrat Iglesias (Informascope, 2017)
A systematic review of literature up to date reflects great scholarly interest in the impacts of study abroad (SA) sojourns on foreign language learners' communicative competence. This paper provides an overview on gains in sociolinguistic and pragmatic competences drawing upon research carried out in this field, which in broad terms supports the belief that both types of competences are effectively developed in SA stays. This article also offers a detailed account of the main constituents of the language tourism product -the travel component and the language learning component- with a special focus on the educational input and the language learning complements included in the latter. Thus, a fundamental part of the language tourism market system will be depicted from a supply perspective. Following an exploratory approach, a literature review was conducted in order to identify existing and missing knowledge in the field of language travel supply, and key aspects were pinpointed and classified.  The taxonomy and underpinning concepts resulting from the categorisation of those key features may be considered the starting point for future investigations on SA programmes. The model offered in this exploratory study aims at constituting the underlying conceptual framework for subsequent research on the role of different SA programme design characteristics within the language tourism experience.